Estimação da curva de Phillips híbrida semiestruturada para inflação de serviços no Brasil: um estudo com bases teóricas novo-keynesiana e monetarista - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study aims to understand the dynamics of the service inflation trough the estimation of semi-structured hybrid Phillips curves for service inflation in Brazil, based on New Keynesian and Monetarist theoretical frameworks. The main motivation lies in the relevant role of service inflation in the Brazilian inflationary process, considering its specific characteristics such as low exposure to external shocks and high inertia. Using quarterly data from 2012 to 2024 and time series econometric techniques, autoregressive distributed lag models were constructed and subjected to stationarity tests and statistical adjustments. The results indicate that, for both the New Keynesian and Monetarist approaches, the variables “lagged headline inflation” and “long-term inflation expectations” were statistically significant. The Monetarist regression showed greater explanatory power (R² = 0.707) and better performance in information criteria (AIC, HQ, and BIC), in addition to normally distributed, homoscedastic residuals and no evidence of severe multicollinearity in both results. These findings highlight the importance of inflation expectations and inflation persistence in the price dynamics of the service sector, offering relevant insights for the conduct of Brazilian monetary policy.
Keywords: Curva de Phillips; Inflação de serviços; Política monetária; Novo-keynesianismo; Monetarismo; Séries temporais; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS